Primary cancers of the small bowel: analysis of prognostic factors and results of surgical management - Talamonti, Mark S; Goetz, Laura H; Rao, Sambasiva; Joehl, Raymond J (Archives of surgery (Chicago. 1960), 2002)
This study was done to review the clinical presentation, surgical management, pathologic features, and prognostic factors for primary small-bowel cancers. Retrospective case series. Tertiary care, university hospital. One hundred twenty-nine patients were surgically treated between January 1, 1977, and December 31, 2000. There were 73 men and 56 women, with a median age of 55 years (age range, 19-82 years). Median follow-up was 36 months. Presenting symptoms and signs, operations performed, and surgical pathologic features were analyzed and survival curves were generated. Clinical findings included abdominal pain (63%), vomiting (48%), weight loss (44%), and gastrointestinal tract bleeding (23%). The distribution of tumors by histological features was as follows: adenocarcinoma (33%), carcinoid tumor (29%), lymphoma (19%), and sarcoma (19%). Cumulative 5-year survival rate was 37% in the adenocarcinoma group, 64% in the carcinoid tumor group, 29% in the lymphoma group, and 22% in the sarcoma group. Significant prognostic predictors of overall survival for the entire cohort and for each tumor subtype included complete resection and American Joint Committee on Cancer tumor stage (P<.05). Patient age, tumor location, histological grade, and use of chemotherapy and radiation therapy did not significantly influence survival. Curative resections were accomplished in 83 patients (64%) with a median survival of 37 months compared with 46 patients undergoing incomplete or palliative resections with a median survival of 10 months (P<.05). Adjacent organ resection was required in 18 (22%) of the 83 patients undergoing potentially curative resections. The median time to recurrence was 16 months. Twenty-one patients (16%) developed associated primary cancers. Aggressive surgical resection in an attempt to achieve complete tumor removal seems warranted. Despite complete resections, patients with high-stage tumors remain at risk for recurrence.